Defiency of natural killer receptor expressing cells in haemophagocytic lymphohistiocytosis - Dunne, Jean (Trinity College (Dublin, Ireland). Department of Immunology, 2002)
Two children, patient A and patient B, were diagnosed on clinical and histological grounds to have haemophagocytic lymphohistiocytosis (HLH) (Henter et al. 1991a; Arico et al. 2001a). Clinical presentation of HLH consists of prolonged fever, failure to thrive, irritability, and hepatosplenomegaly (Henter et al. 1991a). Parental consanguinity indicated a diagnosis of familial haemophagocytic lymphohistiocytosis (FHL) in the case of patient A. Following the development of an Epstein-Barr virus (EBV)-driven lymphoma the diagnosis of patient B was altered to EBV-lymphoma associated haemophagocytic syndrome (EBV-LAHS). The two young patients lacked NK cells and had reduced CD8+ T cells at presentation. They both suffered from recurrent infections most notably with Herpes family viruses.
Keywords: Immunology, Ph.D.; Ph.D. Trinity College Dublin